Atmospheric cold plasma dissipation efficiency of agrochemicals on blueberries. (December 2017) - Sarangapani, Chaitanya; O'Toole, Grainne; Cullen, P.J.; Bourke, Paula
Abstract: Cold plasma has emerged as a potential bio-decontamination technology for microbial and chemical risks associated with food products such as fruits and vegetables. This study investigated the efficacy of cold plasma treatment for the degradation of pesticides (boscalid and Imidacloprid) on blueberries in tandem with the need to retain critical quality attributes of a fresh high value berry product post treatment. An in-package high voltage dielectric barrier discharge plasma reactor was employed for this study. The degradation efficacy of pesticides after 80 kV and 5 min of cold plasma treatment were found to be 80.18% for boscalid and 75.62% for Imidacloprid. Total phenol and flavonoid contents of blueberries increased significantly for 1 min treated samples for all applied voltages. However, plasma treatment significantly decreased the ascorbic acid at longer plasma doses. There was no significant effect on physical parameters such as color while acceptable changes were observed in blueberry firmness. This study demonstrates effective chemical decontamination of blueberries whilst maintaining critical nutritional and physical quality parameters, offering an alternative process for quality retention of processing sensitive high value berry products. Highlights: Cold plasma efficiently degraded pesticides on blueberries. The degradation achieved was 80% for boscalid and 76% for Imidacloprid. Polyphenolic and flavonoid contents increased after 1 min of cold plasma treatment. Cold plasma treatments of up to 5 min had minimal impact on blueberry quality. Cold plasma presents a unique processing tool for agrochemical and biocontrol that retains nutritional quality parameters.